How Are Substrate Binding and Catalysis Affected by Mutating Glu127 and Arg161 in Prolyl-4-hydroxylase? A QM/MM and MD Study - Timmins, Amy; de Visser, Sam P. (Frontiers in Chemistry, 2017)
Prolyl-4-hydroxylase is a vital enzyme for human physiology involved in the biosynthesis of 4-hydroxyproline, an essential component for collagen formation. The enzyme performs a unique stereo- and regioselective hydroxylation at the C4 position of proline despite the fact that the C5 hydrogen atom should be thermodynamically easier to abstract. To gain insight into the mechanism and find the origin of this regioselectivity, we have done a quantum mechanics/molecular mechanics (QM/MM) study on wildtype and mutant structures. In a previous study [Timmins, Saint-André and de Visser, J. Am. Chem. Soc. 2017] we identified several active site residues critical for substrate binding and positioning. In particular, the Glu127 and Arg161 were shown to form multiple hydrogen bonding and ion-dipole interactions with substrate and could thereby affect the regio- and stereoselectivity of the reaction. In this work, we decided to test that hypothesis and report a QM/MM and molecular dynamics (MD) study on prolyl-4-hydroxylase and several active site mutants where Glu127 or Arg161 are mutated for Asp, Gln or Lys. Thus, the R161D and R161Q mutants give very high barriers for hydrogen atom abstraction from any proline C–H bond and therefore will be inactive. The R161K mutant, by contrast, sees the regio- and stereoselectivity of the reaction change but still is expected to hydroxylate proline at room temperature. By contrast, the Glu127 mutants E127D and E127Q show possible changes in regioselectivity with the former being more probable to react compared to the latter.